Energy and biochar co-production from municipal green waste gasification: A model applied to a landfill in the north of Italy. (1st May 2019) - Pedrazzi, Simone; Santunione, Giulia; Minarelli, Andrea; Allesina, Giulio
Highlights: Green waste gasification was experimentally validated through a small scale gasifier. Results show a gasifier electrical efficiency of 16.22% and a stable running. A scenario with a gasifier coupled with a landfill biogas power plant is presented. The full scale gasifier cost is 5 M€ and the investment payback time is 6 years. Gasification biochar has proven to be an excellent fertilizer for basil growth. Abstract: This work discusses the advantages that can be obtained from the integration of landfill gas with biomass gasification. The case study presented consists of a landfill located in the province of Reggio Emilia, in the north of Italy. Landfill gas from municipal-waste fuels four internal combustion engines with overall nominal power of 2 MW, the electricity is sold back to the grid, while the thermal power is used for the heating of an industrial greenhouse compartment for basil production. Within the same facility, green waste is collected from the surrounding municipalities then chipped and sieved. Fine particles are disposed into a composting plant close by, while the sieved fraction is sold to the market for electricity production in large-scale boiler-based power plants. The idea here presented and discussed consists of the implementation of a gasifier to convert the sieved fraction of green waste into a syngas fuel directly on site. Syngas is blended with the landfill gas and then fed to the gas engines. In this work green waste gasification is tested in a commercial small-scale gasifier, proving that sifted green waste is a suitable fuel for this application. A specific consumption of 1.2 kg/kWh and a total electrical efficiency of 16.22% were measured. The sizing of the full-scale gasification facility is based on both the experimental results and data about the local availability of green waste. The economic return of the investment is then discussed. Finally, a further level of integration between gasification and the existing site is proposed: gasification-derived biochar is investigated as soil amendment for the on site company at the landfill that grows basil commercially. Results of 55 days in vivo tests show an increase in the biomass production of the basil of 53% compared to the control test group.